Аналіз сучасного стану та тенденції розвитку ринку джинсів в Україні - Чернобровкіна, Світлана Віталіївна; Синельникова, Діана Максимівна (НТУ "ХПІ", 2018)
Проведено дослідження сучасного стану ринку джинсів в Україні. Для аналізу розглянуто іноземні та українські торгові марки джинсів, що представлені на споживчому ринку України. У процесі дослідження було зроблено огляд світових та українських брендів, а також аналіз позиції, частки ринку основних торгових марок джинсів, що представлені на ринку України, їх асортимент та ціни. Представлено динаміку продажів джинсів у фірмових магазинах міста Харкова.

A study of the current state of the jeans market in Ukraine was conducted. For analysis, foreign and Ukrainian trademarks of jeans presented in the consumer market of Ukraine are considered. In the process of the survey, a review of world and Ukrainian brands was made, and the positions, market shares of the main brands of jeans presented in the Ukrainian market, their assortment and prices were examined. Listed the world's leading brands which occupy leading positions in the Ukrainian jeans market. Information on the state and development of denim clothing industry is presented. The tendency of changes in the values and lifestyle of consumers is observed. The main factors when buying clothes for the buyer are determined. The dynamics of sales of jeans in the Kharkov branded stores is presented. The forecast of sales of jeans for the future period is made.
Analysis of the modern state and trends of the development of the jins market in Ukraine
Keywords: дослідження; торгова марка; частка ринку; асортимент; ціна; trade mark; market share; assortment; price